1999
DOI: 10.1007/pl00005485
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin and tolerance to delay of reward in rats

Abstract: These effects on tolerance to delay may be accounted for by a subtle balance between the opposing functional consequences of pre- versus post-synaptic 5-HT(1A) receptor activation or blockade. Overall, the present results provide further support to the idea that 5-HT processes participate in the control of impulsive-related behaviour, as assessed from tolerance to delay of reward in this particular T-maze procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
144
1
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 223 publications
(154 citation statements)
references
References 2 publications
6
144
1
2
Order By: Relevance
“…However, the behavioral effects of the acute systemic administration of SSRIs on impulsive behavior were not consistent. For example, some studies showed the administration of SSRIs increased the selection rate of a large, delayed reward over a small, immediate reward, indicating a decrease in impulsive choice (Bizot et al, 1988(Bizot et al, , 1999. By contrast, a lack of effect has also been reported (Evenden and Ryan, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…However, the behavioral effects of the acute systemic administration of SSRIs on impulsive behavior were not consistent. For example, some studies showed the administration of SSRIs increased the selection rate of a large, delayed reward over a small, immediate reward, indicating a decrease in impulsive choice (Bizot et al, 1988(Bizot et al, , 1999. By contrast, a lack of effect has also been reported (Evenden and Ryan, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Central 5-HT manipulations also affect the ability to wait for reinforcement following response in impulsive-choice paradigms, although the evidence is less clear cut than for tests in which responding itself must be withheld. Although some studies have found direct effects of 5-HT manipulations on impulsive choice (Bizot et al, 1999;Mobini et al, 2000a, b;Schweighofer et al, 2008;Wogar et al, 1993), others found no such effects (Crean et al, 2002;Tanaka et al, 2007;Winstanley et al, 2004a). This discrepancy has been attributed to subtle differences between tasks.…”
Section: -Ht Depletion Impairs Waiting But Not Ssrt Dm Eagle Et Almentioning
confidence: 99%
“…Briefly, studies with experimental rodents have shown that depleting forebrain 5-HT leads to consistent choices of small, immediate rewards over large, delayed rewards, possibly reflecting hypersensitivity to the delay (Wogar et al, 1993;Mobini et al, 2000;Cardinal et al, 2004;Denk et al, 2005;Cardinal, 2006) (but see Winstanley et al, 2003). Conversely, increasing 5-HT function with the 5-HT indirect agonist fenfluramine decreases impulsive choice (Poulos et al, 1996;Bizot et al, 1999); and 5-HT efflux was found to be increased in the medial PFC (though not OFC) during delay discounting, as measured with microdialysis (Winstanley et al, 2006b). In line with this proposal and animal work, Schweighofer et al (2008) have recently shown that ATD also steepens delayed reward discounting in humans, resulting in increased choice of the more immediate small rewards (but see Crean et al (2002), who used hypothetical rather than experiential choices).…”
Section: Intertemporal Choicementioning
confidence: 99%